Kick-starting a second green revolution in Bengal [India]. - Mukherji, Aditi; Shah, Tushaar; Banerjee, Partha Sarathi (2012)
Two decisions taken by the Government of West Bengal, one, to facilitate easier extraction of groundwater, and the other, the application of a fixed connection fee for an electricity connection to farmers could well lead to a quantum leap in agricultural production.